PERLAWANAN KULTURAL TERHADAP WACANA HEGEMONIS: KAJIAN WACANA FEMINISME DALAM KARYA SASTRA BERWARNA LOKAL BALI - Adhi Dwipayana; Ade Asih Susiari Tantri; I Nyoman Sudiana (Universitas Pendidikan Ganesha, 2024)
This research explores the cultural resistance of Balinese women in literary works. This research adopts the sociological theory of literature and feminist discourse as an analytical framework for studying literary works. The main aim of this study is to analyze various forms of resistance carried out by Balinese women, as represented in literary works, against patriarchal norms that are deeply rooted in Balinese culture. This research implements a qualitative approach to analyze three literary works. The data analysis method used is descriptive qualitative, which involves operational steps, namely interpretation and classification, data presentation, and drawing conclusions. These three literary works were chosen as primary data sources because they contain ideological content regarding the discourse of Balinese women's resistance to patriarchal ideology. The data collection method in this research was carried out through literature study using reading and note-taking techniques. The findings of this research reveal that literary works contain significant elements of resistance, which depict women's courage and determination in facing discrimination and injustice. Apart from that, this research also reveals how the author uses language and cultural symbols to convey a feminist message, providing new insights into the social and cultural dynamics in Bali. This research has significance for a deeper understanding of the position and role of women in Balinese society, as well as presenting a new perspective in the study of feminism and cultural literature. The findings obtained emphasize the importance of literature as a means of resistance and self-expression for women in traditional cultural contexts. Keywords : Cultural resistance, Balinese women, feminist discourse. ABSTRAK Penelitian ini mengeksplorasi perlawanan kultural perempuan Bali dalam karya sastra. Penelitian ini mengadopsi teori sosiologi sastra dan wacana feminisme sebagai kerangka analisis untuk mengkaji karya sastra. Tujuan utama dari studi ini adalah untuk menganalisis berbagai bentuk perlawanan yang dilakukan oleh perempuan Bali, sebagaimana direpresentasikan dalam karya sastra, terhadap norma-norma patriarkal yang telah mengakar dalam budaya Bali. Penelitian ini mengimplementasikan pendekatan kualitatif untuk menganalisis tiga karya sastra. Metode analisis data yang digunakan adalah deskriptif kualitatif, yang melibatkan langkah-langkah operasional, yakni interpretasi dan klasifikasi, penyajian data, serta penarikan kesimpulan. Ketiga karya sastra ini dipilih sebagai sumber data primer karena mengandung muatan ideologis tentang wacana perlawanan perempuan Bali terhadap ideologi patriarki. Metode pengumpulan data dalam penelitian ini dilakukan melalui studi kepustakaan dengan teknik membaca dan mencatat. Temuan dari penelitian ini mengungkapkan bahwa karya sastra memuat elemen-elemen perlawanan yang signifikan, yang menggambarkan keberanian dan keteguhan perempuan dalam menghadapi diskriminasi serta ketidakadilan. Selain itu, penelitian ini juga mengungkap bagaimana penulis menggunakan bahasa dan simbol-simbol budaya untuk menyampaikan pesan feminis, memberikan wawasan baru tentang dinamika sosial dan kultural di Bali. Penelitian ini memiliki signifikansi terhadap pemahaman yang lebih mendalam mengenai posisi dan peran perempuan dalam masyarakat Bali, serta menyajikan perspektif baru dalam kajian feminisme dan sastra kultural. Temuan yang diperoleh menekankan pentingnya literatur sebagai sarana perlawanan dan ekspresi diri bagi perempuan dalam konteks budaya tradisional.